EFFECTIVENESS OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION ON PAIN INTENSITY IN PATIENTS WITH PRIMARY DYSMENORRHEA (The Research of Medical Science Review, 2025)
The main purpose of this study is to check effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) on pain intensity in female undergraduates with primary dysmenorrhea. This is a randomized control study including 100 participants with primary dysmenorrhea lasting for 3 days equally. They were randomly divided into two groups: Transcutaneous Electrical Stimulation (TENS) and Control. Subjects in TENS group were treated with Conventional TENS for 15 minutes once daily while the other group has no treatment. Patients were treated for first 3 days, the severity of pain was examined by Visual Analogue Scale (VAS) in both groups pre-treatment and post-intervention. The data obtained in analyzed through Statistical Packages for Social sciences. Descriptive statistics was used to the participant’s age, Primary dysmenorrhea history, menstrual history, duration of periods, regularity, family history of dysmenorrhea and Day 1 average pain. Independent T test is further used to compare pain intensity of session 1, 2 and 3 between Experimental group and control group. Alpha was set at < 0.05. Results of this study showed Transcutaneous Electrical Nerve Stimulation (TENS) group has significant reduction in pain intensity between pre-treatment and post-intervention (P<0.001). Also there was a significant difference in pain intensity of session 1, 2 and 3 between Experimental group and Control group with (P<0.001). Transcutaneous Electrical Nerve Stimulation (TENS) was found to be effective modality in treating primary dysmenorrhea among female undergraduates.